Efficient Equipment Management for Biomedical Engineering Department in the Hospital - Aruna, M.; Gunasilan, Uma; Naeem, Sadia (International Review of Management and Marketing, 2018)
Biomedical equipment management is a significant concern for safety and worth in the current hospital operations environment. In effect, the practice of an efficient information system will effectually stimulate the managing performance. The drive of this approach is to outline an efficient equipment management that affords for the safe and steadfast operation of medical equipment used in the treatment of patients. In this research work, AlGarhoud Private Hospital's biomedical engineering department, UAE is taken into consideration. This particular establishment is chosen due because it meets the criteria of being a private medical organization that is currently undergoing a revamp in their equipment management system. Collections of data and information dating back from 2010 have been compiled and analyzed. Firstly, the focus has been on asset management. Currently, medical equipment's inventory is managed on Microsoft Excel. Data from 2017 states that there are a total of 900 medical equipment's, and hence reflects its important to manage inventory effectively. Since inventory is getting managed manually, there have been recorded high chances of human error to miss out an important update or maintenance schedule every month. A new software named as Enterprise Asset Management (EAM) has been recommended to resolve this particular issue. Keywords: Efficient Equipment Management, Enterprise Asset Management, EAM JEL Classification: O3